Lady E.S. Drower's Scholarly Correspondence : an Intrepid English Autodidact in Iraq. - Buckley, Jorunn Jacobsen (Studies in the history of religions, 2012)
An edition of the scholarly letters of the English Lady E.S. Drower, famous for her novels, travel accounts, and studies in the Middle East, especially on the Mandaeans. Drower (1879-1972) kept up a lively correspodence with scholars, and the letters here span the years 1938 to the mid-1960s.